Shadow Banking Sharia For Financial Cycle Resilience in Indonesia - Edwin Basmar; Muhamad Takhim; Erlin Basmar; Carl M. Campbell III (Universitas Wahid Hasyim, 2023)
Sharia shadow banking is a good example in managing the level of banking soundness in Indonesia, based on measuring financial activity through Bank Indonesia report data in a time series from 2019 to 2022, it was found that the results of research conducted using the development of the Ed Waves Index model showed that financial activity Islamic banking can continue to run, even though the waves of the financial cycle (macroeconomic variables) are experiencing an acute level of financial depression (monetary crisis and the Covid-19 pandemic) both internally and externally, where the reaction to the pressure of Islamic banking financial activity moves normally with a range between 0.010 Amplitude to -0.015 Amplitude, based on the category of unidirectional reactions in the first period, contra (opposite) reactions in the second period, normal reactions in the third and finally unidirectional reactions in the fourth period. The implications of the movement of this wave of Islamic banking activity are able to contribute to economic growth and financial stability in Indonesia.